Information content of intangible non-current assets : Evidence during economic crisis period in Malaysia - Zaleha Abdul Shukora; Hamezah Md Nora; Muhd Kamil Ibrahim; Jagjit Kaur (Journal of Accounting, Business and Management (JABM), 2005)
This paper examines value-relevance and information content of capitalized intangible non-current assets (INCA). Specifically, we investigate the changes in the information content of INCA due to changes in the economic environment among firms listed on the main board of Bursa Malaysia. The empirical method use time-varying and fixed effects models for the period 1995-1999. Our focus is investigating the information content of INCA during the economic crisis period of 1997-1998 in Malaysia. Based on the association of analysts earnings forecasts errors (AFE) with capitalized INCA, we find evidence of increase information content on INCA during economic crisis periods compared to pre-crisis periods.